Advances in the synthesis and applications of porous carbon materials - Ni, Mei; Zhou, Lei; Liu, Yancen; Ni, Runtao (Frontiers in Chemistry, 2023)
Porous carbon materials have the advantages of high specific surface area, adjustable physicochemical properties, high porosity, good stability and availability. The preparation method of porous carbon materials and the choice of precursors directly determines their properties and range of applications. This article introduced the main methods for the preparation of porous carbon materials and their applications in adsorption, energy storage and catalysis.